With computed tomography confirmed anterolateral left ventricular pseudoaneurysm in patient with dilatative alcoholic cardiomyopathy - Letonja, Mitja (Radiology and oncology (Ljubljana), 2011)
Background. Pseudoaneurysms are rare complications of myocardial infarction with propensity for rupture. There is still a challenge with which diagnostic imaging we performed a final diagnosis of pseudoaneurysm and differentiate it from true aneurysm what is clinically important due to the different treatment. Case report. We presented the unusual case of a 56-year-old man with signs of decompensated heart failure which had worsened a few months before hospitalization. We believed that during worsening of symptoms the patient suffered a silent myocardial infarction complicated by subacute free wall rupture which resulted into left ventricular pseudoaneurysm formation without tamponade. Echocardiography showed dilatativecardiomyopathy which was already present years before and a very rare location of the left ventricular pseudoaneurysm on the anterolateral part of the left ventricle. Pseudoaneurysm was confirmed with CT scan. Due to the severity of contractile dysfunction and no response in treatment for congestive heart failure the directive for the resection was tempered and the patient died due to the progressive heart failure and embolic phenomena. Conclusions. This report shows the importance of non-invasive imaging diagnostic evaluation of acute decompensated heart failure where echocardiography and chest X-ray are the first diagnostic steps. Based on those findings further imaging diagnostic steps must be performed such as CT scan in our case which finally confirms left ventricular pseudoaneurysm with dilatative cardiomyopathy.
Keywords: cardiovascular disease; diagnostika; ehokardiografija; kardiovaskularne bolezni; računalniška tomografija; slikovna diagnostika